Software service and application engineering : Essays dedicated to bernd krämer on the occasion of his 65th birthday - Heisel, Maritta (Lecture Notes in Computer Science, 2012)
This festschrift volume, published in honor of Bernd Krämer on the occasion of his 65th birthday, contains 11 contributions by close scientific companions. Covering topics like Petri nets and theoretical computer science, software and service engineering, cloud computing, and e-learning, the articles presented span the range of the scientific work of Bernd Krämer.